Eleventh workshop on geothermal reservoir engineering: Proceedings - Ramey, H.J. Jr.; Kruger, P.; Miller, F.G.; Horne, R.N.; Brigham, W.E.; Counsil, J.R. (Stanford Geothermal Program) (Stanford University, 1986)
The Eleventh Workshop on Geothermal Reservoir Engineering was held at Stanford University on January 21-23, 1986. The attendance was up compared to previous years, with 144 registered participants. Ten foreign countries were represented: Canada, England, France, Iceland, Indonesia, Italy, Japan, Mexico, New Zealand and Turkey. There were 38 technical presentations at the Workshop which are published as papers in this Proceedings volume. Six technical papers not presented at the Workshop are also published and one presentation is not published. In addition to these 45 technical presentations or papers, the introductory address was given by J. E. Mock from the Department of Energy. The Workshop Banquet speaker was Jim Combs of Geothermal Resources International, Inc. We thank him for his presentation on GEO geothermal developments at The Geysers. The chairmen of the technical sessions made an important contribution to the Workshop. Other than Stanford faculty members they included: M. Gulati, E. Iglesias, A. Moench, S. Prestwich, and K. Pruess. The Workshop was organized by the Stanford Geothermal Program faculty, staff, and students. We would like to thank J.W. Cook, J.R. Hartford, M.C. King, A.E. Osugi, P. Pettit, J. Arroyo, J. Thorne, and T.A. Ramey for their valued help with the meeting arrangements and preparing the Proceedings. We also owe great thanks to our students who arranged and operated the audio-visual equipment. The Eleventh Workshop was supported by the Geothermal Technology Division of the U.S. Department of Energy through Contract DE-AS03-80SF11459. We deeply appreciate this continued support. January 1986 H.J. Ramey, Jr. P. Kruger R.N. Horne W.E. Brigham F.G. Miller J.R. Counsil